BASEMENT OF JUNGGAR BASIN: EVIDENCE FROM DETRITAL ZIRCONS IN SANDSTONE OF PREVIOUS DEVONIAN KALAMAILI FORMATION - Li Y.P.; Li J.Y.; Sun G.H.; Zhu Z.X.; Yang Z.Q. (My University, 2007)
There has been a hot-debated issue on the tectonic attribute and ages of the basement of Junggar basin in geological field for a long time. On the basis of Paleozoic regional geological setting, the authors believe that the provenance of Middle Silurian to lower Carboniferous shallow-sea terrigenous clastic sequences, which are exposed in the regions south of the Kalamaili ophiolite belt in East Junggar, may be located in the east part of Junggar basin. So, SHRIMP U-Pb dating of detrital zircons from the sandstone in the Kalamaili formation of the sequences, which is classified by 1 : 200,000 regional geological survey into the middle Devonian in geological time, can obtain the information on the features of the basement of Junggar basin. 86 detrital zircons yield 89 apparent 206Pb/238U or 206Pb/207Pb ages between (327 ± 8) Ma and (3073 ± 10) Ma, mainly distributed between 320 Ma and 540Ma with many peaks, a dominant peak at 365Ma and some lesser spikes at between 460-480Ma, 510-520Ma, and 530-540Ma, respectively. In addition, 22 older zircons with ages older than 550Ma are found. Of them, four grains with apparent ages from 550Ma to 690Ma, eight grains with from 827Ma to 1083Ma, two grains with 1513Ma, and 1700Ma, two with 1994Ma and 2051Ma, three with from 2464Ma to 2490Ma, and three with from 2876Ma to 3073Ma, respectively. According to petrology of the studied sample, CL images and apparent ages of dated zircons, in combination with regional geological magmatic activities, the authors come to the following preliminary conclusions: (1) it is possible that the deposition of the studied sandstone is in the late of the early Carboniferous not Devonian, and its debris come from the eastern Junggar basin, (2) the provenance of the sandstone is probably composed of Carboniferous to Ordovician mid-acid magmatic rocks, Cambrian to middle Neoproterozoic and early Neoproterozoic to Mesoproterozoic magmatic complexes, and supposedly minor early Precambrian rocks, indicating that the basement of Junggar basin is tectonically a Paleozoic magmatic are imposed upon the Pre-Ordovician continental crust.
Keywords: BASEMENT; DETRITAL ZIRCONS; JUNGGAR BASIN; KALAMAILI FORMATION; PROVENANCE; SANDSTONE; SHRIMP U-PB DATING; Devonian; Paleozoic::Devonian; Палеозой::Девонская